2018
DOI: 10.3390/ijerph15102250
|View full text |Cite
|
Sign up to set email alerts
|

The Risk-Taking Propensity of Construction Workers—An Application of Quasi-Expert Interview

Abstract: High accident rates have been a complicated and persistent problem in the Hong Kong construction industry. This situation has stimulated this investigation into factors that influence the risk-taking propensity of construction workers. However, interviewing workers who had a bad experience is problematic because changes in attitude and perception may occur as a result of such an experience. Using quasi-expert interviews can reduce this problem. The objective of this study was to identify factors that influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
3
20
0
2
Order By: Relevance
“…It is important for each worker to be equipped with proper and adequate PPE and has been thoroughly trained in safe work practices when working on scaffolding. With regards to supervision, this study agreed with Low et al (2018) in that safety supervision and inspection should be referred to frequency, broadness, and depth of safety supervisions and inspections on site. This is in line with Fung et al's (2005) study that there is a highly negative no correlation between safety supervision and risk-taking behavior among construction workers in Hong Kong.…”
Section: Background Of Respondentssupporting
confidence: 66%
See 1 more Smart Citation
“…It is important for each worker to be equipped with proper and adequate PPE and has been thoroughly trained in safe work practices when working on scaffolding. With regards to supervision, this study agreed with Low et al (2018) in that safety supervision and inspection should be referred to frequency, broadness, and depth of safety supervisions and inspections on site. This is in line with Fung et al's (2005) study that there is a highly negative no correlation between safety supervision and risk-taking behavior among construction workers in Hong Kong.…”
Section: Background Of Respondentssupporting
confidence: 66%
“…This is in line with Fung et al's (2005) study that there is a highly negative no correlation between safety supervision and risk-taking behavior among construction workers in Hong Kong. Low et al (2018) suggested that the management should be aware of the problems related to safety supervision and inspection, such as employing additional human resources to ensure adequate safety supervision and inspection for construction workers, thereby reducing their risktaking propensity. In addition, the management should also ensure effective communication with regards to scaffold such as hazard communication through briefing, training, and instructions.…”
Section: Background Of Respondentsmentioning
confidence: 99%
“…Risk perception is defined as the subjective judgment that one makes about the frequency and severity of particular risks [23]. It has been considered an important factor in explaining construction worker risk-taking behavior in qualitative studies [13,24]. However, no studies have been conducted to examine the effect of risk perception on construction worker risk-taking behavior through a quantitative approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Safety climate is the reflection of the attitudes, beliefs, perceptions, and values that employees share in relation to safety [27]. In a previous qualitative study on the risk-taking propensity of construction workers [24], safety climate was found to be one of the main reasons why construction workers take risks at work. Apart from safety climate, work condition was found to be an important factor that influences construction worker risk-taking behavior [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To identify factors affecting the risk-taking behaviour of workers, several studies have investigated the reasons why they conduct such behaviour [8,9,10,11,12,13]. Factors influencing the risk-taking propensity of workers include safety supervision and inspection, safety culture of working environments, social influence, workplace conditions, attitude of workers towards risk, risk perception, and self-perceived easiness of risk-taking behaviour [8,9]. Jiang and Han [10] report that the preconditions for unsafe acts, unsafe supervision, and organisational influences resulted in unsafe behaviour.…”
mentioning
confidence: 99%